Removal of Chromium Cr(VI) by Fe3O4 Hollow Spheres from Wastewater - Wu, Ying; Han, Chengliang (Asian Journal of Chemistry, 2012)
In present work, Fe3O4 hollow spheres were prepared and characterized. The adsorption properties of Cr(VI) on Fe3O4 hollow spheres have been studied and the effects of varying the dosage and pH on the adsorption process have been investigated. The reproducibility of the adsorption process and the adsorption mechanism were also studied. It was found that the removal ratio of Cr(VI) increased with increasing dosage of Fe3O4 hollow spheres. The optimal pH value was found to be 4. Adsorption isotherm was consistent with the Langmuir equation. The adsorption process was mainly physical one and redox reaction was also involved. It was suggested that the Fe3O4 hollow spheres is a promising adsorbent for Cr(VI).